Justice for Child Victims of Violence in the Pesantren Environment (Study of Decision Number 5642 K/Pid.Sus/2022): Keadilan bagi Anak Korban Kekerasan di Lingkungan Pesantren (Studi atas Putusan Nomor 5642 K/Pid.Sus/2022) - Cahya Wulandari; Sukadari Sukadari; Winarsih, Winarsih; Chanidia Ari Rahmayani (Universitas Negeri Semarang, 2025)
Violence against children in educational environment, including Islamic boarding schools, is a serious issue with long-term impacts on children's physical, psychological, and social development. Forms of violence include physical, psychological, sexual, and bullying, which, although often unseen, can cause trauma, mental disorders, decreased academic performance, and even deviant behavior in the future. This research aims to analyze efforts to prevent violence against children in Islamic boarding schools based on child protection policies, and to examine fair law enforcement through a study of Supreme Court Decision Number 5642 K/Pid.Sus/2022. The method used is empirical legal, combining the analysis of legislation with field facts. The research findings indicate that preventing violence requires synergy between the government, pesantren caretakers, families, and society through legal socialization, fostering a safe environment, enhancing educators' capacity, and providing reporting mechanisms such as the Bullying Box. A legal analysis of Supreme Court Decision No. 5642 K/Pid.Sus/2022 revealed that the defendant, an educator, was found guilty of repeated sexual violence against 12 underage female students and sentenced to death. This decision affirms the application of the principle of the best interest of the child through the awarding of restitution, the handover of the victim baby's custody to the local government, and the prohibition of victim blaming. Law enforcement in this case combines legal certainty, utility, and justice, not only punishing the perpetrator but also restoring the victim, providing a deterrent effect, and strengthening the commitment to child protection in religious-based educational environments.